Fitness impact and stability of a transgene conferring resistance to dengue-2 virus following introgression into a genetically diverse Aedes aegypti strain. - Alexander W E Franz; Irma Sanchez-Vargas; Robyn R Raban; William C Black; Anthony A James; Ken E Olson (Public Library of Science (PLoS), 2014)
In 2006, we reported a mariner (Mos1)-transformed Aedes aegypti line, Carb77, which was highly resistant to dengue-2 virus (DENV2). Carb77 mosquitoes expressed a DENV2-specific inverted-repeat (IR) RNA in midgut epithelial cells after ingesting an infectious bloodmeal. The IR-RNA formed double-stranded DENV2-derived RNA, initiating an intracellular antiviral RNA interference (RNAi) response. However, Carb77 mosquitoes stopped expressing the IR-RNA after 17 generations in culture and lost their DENV2-refractory phenotype. In the current study, we generated new transgenic lines having the identical transgene as Carb77. One of these lines, Carb109M, has been genetically stable and refractory to DENV2 for >33 generations. Southern blot analysis identified two transgene integration sites in Carb109M. Northern blot analysis detected abundant, transient expression of the IR-RNA 24 h after a bloodmeal. Carb109M mosquitoes were refractory to different DENV2 genotypes but not to other DENV serotypes. To further test fitness and stability, we introgressed the Carb109M transgene into a genetically diverse laboratory strain (GDLS) by backcrossing for five generations and selecting individuals expressing the transgene's EGFP marker in each generation. Comparison of transgene stability in replicate backcross 5 (BC5) lines versus BC1 control lines demonstrated that backcrossing dramatically increased transgene stability. We subjected six BC5 lines to five generations of selection based on EGFP marker expression to increase the frequency of the transgene prior to final family selection. Comparison of the observed transgene frequencies in the six replicate lines relative to expectations from Fisher's selection model demonstrated lingering fitness costs associated with either the transgene or linked deleterious genes. Although minimal fitness loss (relative to GDLS) was manifest in the final family selection stage, we were able to select homozygotes for the transgene in one family, Carb109M/GDLS.BC5.HZ. This family has been genetically stable and DENV2 refractory for multiple generations. Carb109M/GDLS.BC5.HZ represents an important line for testing proof-of-principle vector population replacement.